ASSESSING THE IMPACT OF ECONOMIC HARDSHIP ON FISHING MOTIVATION AMONG FISHERMEN IN NIGER DELTA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
The Niger Delta region is heavily reliant on fishing for both economic stability and food security. However, economic hardship, driven by factors such as fluctuating oil prices, environmental degradation, and socio-political instability, has significantly impacted the livelihoods of fishermen. This study aims to assess the impact of economic hardship on the motivation of fishermen in the Niger Delta.  A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 300 fishermen across various communities in the Niger Delta between January and June 2024. The survey included questions on economic conditions, fishing practices, and motivational factors. Qualitative interviews provided deeper insights into the personal experiences and challenges faced by the fishermen. Data were analyzed using SPSS version 25.0 and thematic analysis. The findings revealed that economic hardship has led to a significant decline in fishing motivation among the fishermen. Approximately 70% of respondents reported reduced motivation due to financial constraints, high costs of fishing inputs, and declining fish stocks. The qualitative data highlighted that many fishermen are considering alternative livelihoods due to the unsustainable nature of their current practices. Key factors influencing motivation included access to credit, market conditions, and support from government and non-governmental organizations. The study underscores the critical impact of economic hardship on fishing motivation in the Niger Delta. Addressing these challenges requires comprehensive strategies, including financial support, improved access to fishing inputs, and sustainable fishing practices. Policymakers and stakeholders must collaborate to create an enabling environment that supports the resilience and motivation of fishermen in the region.